Exploring the potential protective and anti-inflammatory effects of the crude ethanolic extract of Annona squamosa Linn fruit against Ethanol-mediated gastric erosion - Hanadi J. Al-Zubaidi; Mohammed T. Mohammed; Aoula Al-Zebeeby; Azhar A. Alkaby; Wurood Razzaq Hassan (Open Veterinary Journal)
Background: Annona squamosa L. is a medically important fruit that belongs to the family Annonaceae and has many medical benefits, including antiulcer effects.